Seasonal analysis of Klobuchar and NeQuick G single-frequency ionospheric models performance in 2018 - Setti Júnior, Paulo de Tarso [UNESP]; Aquino, Marcio; Veettil, Sreeja Vadakke; Alves, Daniele Barroca Marra [UNESP]; Silva, Crislaine Menezes da [UNESP] (Elsevier, 2020)
For single frequency positioning, the ionospheric effects can be minimized by using an ionospheric model, e.g., the Klobuchar or the NeQuick G. These models, respectively associated with the Global Positioning System (GPS) and Galileo systems, are based on a set of transmitted coefficients that describe the background ionospheric behavior and can be used to estimate the ionospheric delay at any time and location on the globe. We evaluate the accuracy and seasonal behavior of the Klobuchar and the NeQuick G models at different latitudes during the solar minimum year of 2018. Calibrated ionospheric Slant Total Electron Content (STEC) values from 33 MGEX (The Multi-GNSS Experiment) stations tracking GPS and Galileo satellites are used as a reference for comparison. The evaluation results show that, for low solar activity conditions (Winter Solstice), the Klobuchar model usually overestimates the ionospheric delay measured on the L1 frequency, with a mean bias of 0.93 m, and performs better than NeQuick G in regions and periods of high ionospheric activity (Spring and Autumn Equinoxes). NeQuick G usually underestimates the delay, with a mean bias of −0.14 m, performing better than Klobuchar in regions and periods of low ionospheric activity. Overall, Klobuchar and NeQuick G presented a modelling error RMS of 1.54 m and 1.19 m respectively.
Keywords: Calibrated STEC; Ionospheric models; Klobuchar; NeQuick G